Pengaruh Penambahan Garam Ikan dan Probiotik terhadap Kualitas Air pada Ikan Guppy (Poecilla reticulata) - Akbar, Adhitya Yoga (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
Ornamental fish cultivation is a promising business area, many people have started ornamental fish cultivation. One of the ornamental fish that is gaining popularity is the guppy fish (Poecilla reticulata). The main problems in guppy fish farming are disease and water quality, both of which play an important role in the success of guppy fish farming. Salt and probiotics are considered capable of improving water quality in guppy fish culture. This study aims to determine the effect of adding fish salt and probiotics on water quality in guppies (Poecilla reticulata). The results showed that giving probiotics to guppies was more effective than using salt.